Mycorrhizal Symbioses Enhance Competitive Weed Growth in Biochar and Nutrient-Amended Soils - O'Neil, Chase M.; Nash, Jake; Tiemann, Lisa K.; Miesel, Jessica R. (Frontiers in Agronomy, 2021)
Abutilon theophrasti (velvetleaf) is a highly competitive weed in agroecosystems that is well-studied for its efficient nitrogen (N) acquisition, yet research on its phosphorus (P) uptake is lacking. One pathway may be through symbioses with arbuscular mycorrhizal fungi (AMF) which increase nutrient acquisition. These AMF benefits can be further enhanced by soil amendment with biochar, although effects may vary with different biochar production characteristics. We implemented a fully factorial nutrient and biochar addition experiment in a greenhouse for six months to determine how AMF nutrient uptake impacts plant growth and how these effects vary between two biochar types. We measured total above- and belowground biomass, plant tissue concentration (N and P), AMF colonization and activity rates, and soil media N and P availability. Overall, we observed few statistically significant results, however AMF N uptake may have been more beneficial to velvetleaf than AMF P uptake as evidenced by increased biomass and tissue N concentrations in treatments where N was only accessible by AMF. Additionally, by maintaining root to shoot ratios biochar may have provided plants with N and P (through sorption of nutrients to surfaces or its inherent properties) when nutrients were more difficult to access. We also found variable plant responses across the two biochar types used. Understanding how nutrient and biochar additions can influence weed competition is important for anticipating potential undesirable consequences of novel soil amendments such as biochar.